2017
DOI: 10.1080/21501203.2017.1369187
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the efficacy of zinc oxide nanoparticles against Penicillium expansum by automated turbidimetric analysis

Abstract: Public concerns about food safety have triggered a worldwide implementation of new legislations aimed at banning many of the most popular food conventional antifungal treatments. There is therefore an urgent need to identify novel and safer solutions to prevent fungal contamination of food. The antifungal effect of zinc oxide nanoparticles (ZnO NPs) against the postharvest pathogenic fungus Penicillium expansum has been investigated in this study. An automated turbidimetric assay, with a standard 96-well micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 26 publications
(43 reference statements)
2
16
1
Order By: Relevance
“…17,27 We used sub-MIC (3±1.7µg/mL) concentrations of ZnO nanoparticles and Nystatin to inhibit the expression of SAP1-3 genes. The results revealed that both ZnO and Nystatin decreased the SAP1-3 genes expression in all isolates that is in accordance with the findings of Cho et al 10,[28][29][30] This finding shows that ZnO nanoparticles 5±1.3µg/mL and Nystatin 3±1.3µg/mL Figure 5 Comparison of the expression of SAP1-3 of VVC C. albicans isolates with 3±1.7µg/mL concentrations of ZnO-nanoparticles and Nystatin compared to the calibrated gene in the control group (Value of the nonadjacent samples was zero). The ACT1 gene was used as an internal control (P<0.05).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…17,27 We used sub-MIC (3±1.7µg/mL) concentrations of ZnO nanoparticles and Nystatin to inhibit the expression of SAP1-3 genes. The results revealed that both ZnO and Nystatin decreased the SAP1-3 genes expression in all isolates that is in accordance with the findings of Cho et al 10,[28][29][30] This finding shows that ZnO nanoparticles 5±1.3µg/mL and Nystatin 3±1.3µg/mL Figure 5 Comparison of the expression of SAP1-3 of VVC C. albicans isolates with 3±1.7µg/mL concentrations of ZnO-nanoparticles and Nystatin compared to the calibrated gene in the control group (Value of the nonadjacent samples was zero). The ACT1 gene was used as an internal control (P<0.05).…”
Section: Discussionsupporting
confidence: 91%
“…3 The yeasts were first identified according to their morphological characteristics using several phenotypic techniques such as production of germ tube in human serum, culture on CHROMagar Candida (Chromagar, France), and Cornmeal agar (Sharlo, USA), containing Tween 80. 10 After identification of primary morphology, DNA extraction was performed using the Phenol-chloroform-isoamyl alcohol method. DNA was amplified using the ITS1 (5ʹ-TCC GTA GGT GAA CCT GCG G-3ʹ) and ITS4 (5ʹ-TCC TCC GCT TAT TGA TAT GC-3ʹ) primers, which were used for PCR amplification of the ITS1-5.8S-ITS2 rDNA region.…”
Section: Sampling Culture and Identification Of Yeastsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the application of ZnO concentrations did not reveal antifungal activities against R. stolonifer. Our results were in accordance with those of others who had demonstrated the fungicidal efficacy of ZnO-NPs against post-harvest pathogens, including Penicillium expansum Yehia and Ahmed, 2013;Sardella et al, 2018) Fusarium oxysporum (Yehia and Ahmed, 2013) and Botrytis cinerea . Also, Jamdagni et al (2018a) stated that green-synthesized ZnO-NPs had a good antifungal activity against Alternaria alternata, Aspergillus niger, Botrytis cinerea, Fusarium oxysporum and Penicillium expansum showing a minimum inhibitory concentration (MIC) of 64, 16, 128, 64 and 128 µg L -1 , respectively.…”
Section: Antifungal Effect Of Zno-npssupporting
confidence: 93%
“…Copper nanoparticles have also been used as antimicrobial against a wide range of microorganisms including bacteria, fungi, and even algae ( Hou et al, 2018 ; Sardella et al, 2018 ). As for AgNPs, the size is related to CuNP activity due to the dramatic increase of the surface/volume ratio, which promote the generation of ROS that trigger cell damage according, such as oxidation of proteins, cleavage of DNA/RNA molecules or lipid peroxidation in membranes ( Shaikh et al, 2019 ).…”
Section: Alternative Antibacterial Therapiesmentioning
confidence: 99%